Системний аналіз дуальності задач фільтрації та управління для одного класу динамічних систем - Pоdladchykov, V. N.; Narodyckaya, N. A. (The National Technical University of Ukraine "Igor Sikorsky Kyiv Polytechnic Institute", 2019)
An analytical solution to problems of filtration and optimal control with a quadratic performance criterion for discrete time systems has been developed.